Dependence of fertility on kisspeptin-Gpr54 signaling at the GnRH neuron - Kirilov, Milen; Clarkson, Jenny; Liu, Xinhuai; Roa, Juan; Campos, Pauline; Porteous, Rob; Schütz, Günther; Herbison, Allan E. (Nature Communications, 2013)
Signaling between kisspeptin and its receptor, G-protein-coupled receptor 54 (Gpr54), is now recognized as being essential for normal fertility. However, the key cellular location of kisspeptin-Gpr54 signaling is unknown. Here we create a mouse with a GnRH neuron-specific deletion of Gpr54 to assess the role of gonadotropin-releasing hormone (GnRH) neurons. Mutant mice are infertile, fail to go through puberty and exhibit markedly reduced gonadal size and follicle-stimulating hormone levels alongside GnRH neurons that are unresponsive to kisspeptin. In an attempt to rescue the infertile phenotype of global Gpr54−/− mutants, we use BAC transgenesis to target Gpr54 to the GnRH neurons. This results in mice with normal puberty onset, estrous cyclicity, fecundity and a recovery of kisspeptin’s stimulatory action upon GnRH neurons. Using complimentary cell-specific knockout and knockin approaches we demonstrate here that the GnRH neuron is the key site of kisspeptin-Gpr54 signaling for fertility.
Gesehen am 22.06.2022